The Hikikomori Phenomenon and Its Evolution in Modern Society: A Systematic Literature Review - esposito, vincenzo (Italian Sociological Review, 2024)
This paper intends to thoroughly examine the phenomenon called Hikikomori., which was initially studied in Japan in the late 1990s (Saito, 1998). Importantly, in recent years there has been a significant surge in current research efforts aimed at investigating the many aspects of this complex phenomenon. This article’s objective is to effectively organize and classify various articles discussing the Hikikomori phenomenon. It considers critical factors such as the type of researcher involved, the specific angle or focus of the article, and the disciplinary perspective underpinning it. By examining these elements, readers can gain a more comprehensive and nuanced understanding of this complex and often misunderstood phenomenon. To achieve our goal, we followed a structured process. Firstly, we extracted articles through Sciilit academic indexing platform. Then, we created an analysis form to enter the collected data. Finally, we analyzed the data using various techniques.